Efficacy of herbal medicines and standard antidepressants on neurotransmitter and behavioral outcomes in animal models of depression (Bangladesh Journal of Pharmacology, 2025)
Herbal-based therapies show potential as antidepressants, though compara-tive efficacy remains uncertain. This study employed a meta-analysis to evaluate the efficacy of herbal interventions against standard antidepressants in animal depression models. A systematic search of PubMed, ScienceDirect, Cochrane, and Google Scholar (up to January 2025) identified 20 eligible studies. The behavior (open field test, tail suspension test) and neurotrans-mitters (serotonin, dopamine, noradrenaline) were analyzed as outcomes. Random-effects models were used, and risk of bias was assessed via SYRCLE. Curcumin improved open field test scores and increased serotonin and noradrenaline levels. Rosemary essential oil showed the strongest effect in the tail suspension test. Anthocyanins enhanced dopamine levels while zinc oxide nanoparticles exhibited effects comparable to curcumin. This finding supports the antidepressant potential of specific herbal, particularly curcumin, rosemary essential oil, and anthocyanins. Further standard research is necessary to confirm clinical relevance.